Pengeruh Model Problem Based Learning Berbantuan Media Educaplay Terhadap Peningkatan Kemampuan Pemahaman Konsep IPAS Murid Kelas IV Sekolah Dasar - Setiawan, Riza; Indriani, Rina; Fazriyah, Nurul (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The problem of low ability to understand science concepts in elementary school students is the basis of this study. The study aims to determine the effect of the Problem Based Learning model assisted by Educaplay media on the ability to understand science concepts in elementary school students. The study used a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of 60 students selected using purposive sampling, consisting of 30 students in the experimental class and 30 students in the control class. Data were collected through a concept understanding test and analyzed using descriptive statistics, t-test, effect size, and N-gain. The results showed that the ability to understand science concepts in the experimental class increased significantly compared to the control class. The effect size value of 0.889 indicates a high influence, while the N-gain results showed that the increase in the experimental class was in the high category and the control class in the medium category. These findings indicate that the Problem Based Learning model assisted by Educaplay media is effective in improving the ability to understand science concepts and can be an alternative for innovative learning in elementary schools.